(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2021)
From the end of the 12th century, in parallel with the transformation of the forms of government, the use of writing in the communal Italian cities increase. This change also affects the production of epigraphic texts. Painted or carved in stone, they are increasingly being displayed in various parts of the city, particularly on public buildings and in other spaces used by the urban government. During the second half of the 13th century, public palaces became the favourite place for the presentation of inscriptions with legal content, which can be traced back to the category of ’carthae lapidariae’, now once again at the centre of historiographical debate. These epigraphical texts have the particularity of proposing, in full or in part, the text of an act. The mural painting dedicated to the Arbitrato di Scolaio Ardinghelli (1292), in the town hall of San Gimignano, offers a new perspective on this type of inscription. Indeed, this representation not only makes it possible to clarify the mode of production and functions of these texts, but also the relationship between the inscription and the document on which it depends.